Targeting proteases involved in the viral replication of SARS-CoV-2 by sesquiterpene lactones from chicory (Cichorium intybus L.). Issue 17 (8th August 2022) - Ávila-Gálvez, María Ángeles; Rafael-Pita, Carlos; Fernández, Naiara; Baixinho, João; Anastácio, José D.; Cankar, Katarina; Bosch, Dirk; Nunes dos Santos, Cláudia
Abstract : Sesquiterpene lactones (STLs) from chicory root extract may inhibit SARS-CoV-2 Mpro and PLpro. Abstract : SARS-CoV-2 is a highly transmissible and pathogenic coronavirus causing a respiratory disease that emerged in 2019, leading to a public health emergency situation which continues to date. The treatment options are still very limited and vaccines available are less effective against new variants. SARS-CoV-2 enzymes, namely main protease (Mpro) and papain-like protease (PLpro), play a pivotal role in the viral life cycle, making them a putative drug target. Here, we described for the first time the potential inhibitory activity of chicory extract against both proteases. Besides, we have identified that the four most abundant sesquiterpene lactones in chicory inhibited these proteases, showing an effective binding in the active sites of Mpro and PLpro. This paper provides new insight for further drug development or food-based strategies for the prevention of SARS-CoV-2 by targeting viral proteases.